Optimizing Career Development and Academic Achievement of Generation Z Students through Strengths-Based Counseling - Annisa, Dona Fitri; Novianti, Williya; Nuramalia, Raras; Irmayanti, Rima (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Generation Z students, who were born and developed in the digital era, face unique challenges in career development and academic achievement. The characteristics of those who tend to rely on technology to communicate and learn often conflict with traditional academic and career expectations. This research aims to analyze the application of strengths-based school counseling in optimizing the potential of Generation Z students. Through a literature review approach, this study evaluates the impact of this approach on their academic motivation and career readiness. The findings show that strengths-based guidance can improve students' self-confidence, coping strategies, and emotional regulation. In addition, this approach, which utilizes digital technology as an interactive medium, provides positive results in supporting the development of student potential. Adapting coaching methods to the unique characteristics of Generation Z, such as their preference for technology and online communication, has been shown to strengthen the effectiveness of this approach. The research conclusions underscore the importance of adaptation in the implementation of strengths-based guidance to address the specific needs of Generation Z students, thereby helping them overcome academic challenges and achieve future career success. This research provides strategic insights for educators and school counselors to support holistic student development in an era that continues to change.